The Sustainability Of Cash Waqf Using Blockchain Technology: A Conceptual Study - Intan Fatimah Anwar; Syarifah Bahiyah Rahayu; Yuslina Yusoff; Noor Faizah Mohd Lajin (Asosiasi Dosen Akuntansi Indonesia (ADAI), 2024)
Non-Indexed Publication